Ultrasonic preparation, structural characterization and functional enhancement of thyme essential oil-loaded microcapsules based on mannosylerythritol lipid-A - Shunjie Kang; Qihe Chen; Haorui Ma; Jiwei Ding; Changchun Hao; Qin Shu; Yongfeng Liu (Ultrasonics Sonochemistry)
Mannosylerythritol lipid-A (MEL-A) is a kind of novel biosurfactant and has great potential to apply into food and pharmaceutical field with its outstanding physicochemical and biological property. In this study, Thyme essential oil (TEO) microcapsules based on MEL-A were prepared through ultrasonic emulsification and characterized by size, morphology, structure, antioxidant and antibacterial activity. The results showed the optimal preparation condition was the duration of 15 min and power intensities of 400 W/cm2 through ultrasound treatment, improving the solubility and applicability of TEO. Further experiment explored the physicochemical properties and biological activity of TEO microcapsules, measuring a particle size of 276.19 ± 1.72 nm with good dispersibility. FT-IR, X-ray, and TEM confirmed the successful encapsulation of the essential oil within the microcapsules. Meanwhile, the antioxidant and antibacterial properties of microcapsules were assayed and microcapsules with 7 % MEL-A exhibited better antioxidant properties, while those containing 13 % MEL-A showed better antibacterial performance. In conclusion, MEL-A showed obvious structural stability and functional enhancement in TEO-loaded microcapsules, indicating that its potential applications in food preservation and food machinery sterilization are numerous.